Evaluating the geological and soil characteristics influencing landslide susceptibility in Anambra state, Nigeria - Benard Ifeanyi , Odoh; Charity Nkiru , Nwokeabia (International Journal of Advanced Geosciences, 2024)
This study investigates soil erodibility in three Local Government Areas (LGAs) within Anambra State, Nigeria—Ekwusigo, Ihiala, and Ogbaru—situated in the lower Niger River Basin prone to frequent and severe flooding. The aim is to assess geological and soil characteristics influencing landslide susceptibility. The methodology involves identifying and characterizing soil types, calculating the Soil Erodibility Factor (K) using empirical formulas, and mapping erosion susceptibility. Data from the Soil Map of the World (version 3.6) were used, corrected for accuracy, and integrated into geographic projections. Analysis included William’s equation to calculate K factors based on soil properties such as sand, silt, clay, and organic matter content. Results highlight diverse geological formations: Ameki Group (34.24%), Benin Formation (0.26%), Ogwashi-Asaba Formation (1.59%), River Niger (1.86%), Sands, Gravels, and Clay (42.36%), and Sombreiro Warri Deltaic Plain (19.69%). Soil types identified include Dystric Nitosols (K = 0.0178) covering 449.11 km² and Gleysols (K = 0.0189) covering 283.95 km², each exhibiting unique erosion susceptibilities. Gleysols are characterized by poor drainage and high-water retention, posing higher landslide risks during heavy rainfall compared to Dystric Nitosols. The correlation between K factors and hydrological data, showing Gleysols as more vulnerable to landslides in wet conditions. Recommendations include targeted erosion control measures like terracing, vegetative buffers, and improved drainage systems for high-risk zones. Maintaining vegetative cover and implementing sustainable land management practices are crucial for mitigating erosion and landslide risks. This study provides a detailed understanding of geological and soil factors affecting landslide susceptibility in Anambra State. It underscores the need for tailored soil conservation and landslide mitigation strategies aligned with specific geological formations and soil types, contributing to sustainable land management practices in flood-prone regions.